Race car count - Dotlich, Rebecca Kai; Slack, Michael, 1969- (New York : Christy Ottaviano Books, Henry Holt and Company, 2015)
"Count to ten with fast and colorful race cars"--
Keywords: Stories in rhyme; Automobiles, Racing -- Fiction; Counting; JUVENILE FICTION / Concepts / Counting & Numbers; JUVENILE FICTION / Transportation / Cars & Trucks